Analysis of acoustic emission amplitude parameters when increasing the machining depth of a composite - Filonenko, Sergiі; Zaritskyi, Oleg (Eastern-European Journal of Enterprise Technologies, 2017)
Optimization and control of technological parameters in the machining of composite materials is an important task to ensure quality of the manufactured products. Studies are undertaken to solve the given problem using the method of acoustic emission. We considered procedure and results of experimental research into parameters of acoustic emission signals when changing the depth of composite machining. It was determined that increasing the depth of composite material machining did not not affect the character of acoustic radiation. Acoustic emission is continuous. However, there occurs an increase in the mean level of amplitude of the registered emission signal and the magnitude of its variability. We determined statistical amplitude parameters of acoustic emission signals at increasing the depth of composite machining. The data approximation was performed and the mathematical notation derived of the regularities at an increase in the mean level of amplitude, its standard deviation and variance with increasing machining depth. It was established that regularities of the increase in the amplitude parameters of acoustic emission signals were well described by nonlinear functions. It was determined that the most sensitive and informative parameter of the registered acoustic emission signals was a variance in the mean level of amplitudes. It is shown that the percentage increase in the variance of the mean level of signal amplitude outpaces the percentage increase in the mean level of amplitude and its standard deviation. The obtained patterns could be used for the optimization of technological processes. When conducting machining ‒ to monitor, control and manage the depth of machining a composite with the assigned structure.